Total synthesis and stereochemical reassignment of dehydromicrosclerodermin B and microsclerodermin J - Melikhova, E (2016)
This thesis describes research towards the total synthesis of two marine natural products, dehydromicrosclerodermin B and microsclerodermin J. The synthesis of the most complex subunit of these peptides, AMMTD, was accomplished in a longest linear sequence of 21 steps starting from (S)-Roche ester. Preliminary results conducted by other group members were improved; the key cuprate displacement reaction and the final steps of the synthetic sequence were developed. Subsequently, AMMTD-GABOB dipeptide was synthesised and coupled with the northern hemisphere. An appropriate protecting group strategy was developed such that macrolactamisation and subsequent protecting group removal could be achieved. This required the design of a new approach to the synthesis of the tryptophan-2-carboxylic acid. An "end-game" strategy, which had previously been developed on model substrates, failed on late-stage cyclic or linear hexapeptides. Because of this, studies turned to the completion of a synthesis of dehydromicrosclerodermin B. Comparison of the data for synthetic and natural dehydromicrosclerodermin B revealed a mistake in the assignment of the (45S)-configuration. The corresponding (45R)-epimer was synthesised and its data were in a good agreement with those of dehydromicrosclerodermin B. Based on the reassignment of the C45 stereocentre of dehydromicrosclerodermin B, the total synthesis of microsclerodermin J containing a reassigned (R)-configured pyrrolidinone unit was accomplished. NMR data for synthetic and natural microsclerodermin J were in complete agreement, confirming that the initial stereochemical assignment of this natural product was incorrect.